EFFICACY OF PHYSICAL TRAINING AND ANALYSIS OF LIPID-LOWERING THERAPY IN PATIENTS WITH ISCHEMIC HEART DISEASE AFTER ACUTE CORONARY INCIDENTS - D. M. Aronov; V. B. Krasnitskij; M. G. Bubnova (Столичная издательская компания, 2016)
Aim. To study efficacy of moderate-intensity physical training (PT) and evaluate lipid-lowering therapy in patients with ischemic heart disease (IHD) after acute coronary events in real practice.Material and methods. A total of 392 patients survived during last 3-8 weeks myocardial infarction, unstable angina or myocardial revascularization were included into the study. Inclusion of patients with stable angina pectoris after hospital treatment was also possible. Patients were randomized to the main (n=197) and control (n=195) groups. Patients of the main group received moderate-intensity PT. All patients received beta-blocker, nitrate, ACE inhibitors and acetylsalicylic acid. Frequency of lipid-lowering therapy prescription and its efficacy were assessed in both groups. Duration of the study was 1 year. The efficacy of interventions was evaluated by the dynamics of plasma lipid levels, results of bicycle ergometry and clinical end points.Results. We observed increase in exercise test duration by 32% (p<0.001), efficiency of heart work by 12% (p<0.05), decrease in frequency of angina attacks by 51% (p<0.001) in the main group. Decrease in total cholesterol (TC) by -3.6% (p<0.05) and increase in high density lipoproteins (HDL) cholesterol by 12.3% (p<0.01) were also observed. Differences in the dynamics of physical tolerance, levels of TC, HDL cholesterol and the TC/HDL cholesterol ratio were significant at intergroup comparison. Lipid-lowering drugs implementation was inadequate in both groups. Target plasma levels of low density lipoproteins (LDL) cholesterol were reached in no one group. We registered less cardiovascular events in the main group in comparison with control one (14% vs 28%, respectively) as well as hospitalizations due to IHD (11% vs 18%, respectively) and number of days of disability (2.2 vs. 4.2 days per patient annually, respectively). Differences in mentioned clinical end point rates were significant between groups (p<0.05).Conclusion. Results of the study shown PT efficacy in patients with IHD after cardiovascular events. Lipid-lowering therapy is conducted inefficiently in patients with IHD in real practice. It is advisable to introduce PT program in real practice as well as adequate pharmacotherapy.